How do Australian universities market STEM courses in YouTube videos?. Issue 2 (3rd July 2019) - Mwenda, Amanda Bridget; Sullivan, Miriam; Grand, Ann
ABSTRACT: Universities are no longer limited to traditional media platforms for recruitment advertising; increasingly, institutions are using online videos and social media to promote themselves locally and internationally. We analysed a sample of 81 YouTube videos that promote Science, Technology, Engineering, and Mathematics (STEM) courses in 40 Australian universities. We used quantitative content analysis to examine gender and ethnic representations, and qualitative content analysis to inductively find marketing themes. Videos used on the websites of both established and younger Australian universities had almost equal numbers of women and men. Students (including alumni) were the most common speakers in videos. However, representation of non-Caucasians remained low. Of the 17 reoccurring themes identified, Course Experience and Labour Market were most common. The lack of clear unique selling propositions was a key weakness across all videos. Overall, video content from Australian STEM faculties rarely went beyond vague platitudes and generally lacked specific STEM content.